Nigeria under structural adjustment - Essien, Efiong (Ibadan, Nigeria : Fountain Publications, 1990)
At the time the book was written, the country was undergoing a political transition in the Third Republic. Its contents therefore, are intended to explain and justify a similar transition in the economy.
Includes bibliographical references and index.
aia 18/05/2018
Loans
Keywords: Structural adjustment; Economic policy; Nigeria